DNA metabarcoding reveals evidence of inter- and intra-guild predation by Scylla paramamosain in a marine ecosystem - Saqib, Hafiz Sohaib Ahmed; Yuan, Ye; Kazmi, Syed Shabi Ul Hassan; Tayyab, Muhammad; Xiang, Zifei; Ikhwanuddin, Mhd; Ma, Hongyu (Frontiers in Marine Science, 2023)
Crustacean predators exhibit diverse trophic interactions across various habitats in aquatic ecosystems. To assess their ecological roles, it is essential to understand their complete dietary spectrum. Recently, DNA-based techniques such as DNA metabarcoding and high-throughput sequencing have provided insights into trophic networks and their response to environmental drivers. In this study, we used these methods to investigate the impact of salinity gradients on the trophic networks of mud crabs (Scylla paramamosain) in marine ecosystems. Our results revealed that mud crabs prey on a wide range of taxa, including crabs (other than the host species), fish, shrimps, and other prey factions. Salinity gradients had a significant influence on the specific prey items, such as high predation on Metapenaeus, and Trigonopterus species in high salinity sites. Notably, crabs exhibited a greater infestation of Portunion parasites in environments with high salinity levels, in contrast to environments with lower salinity levels. Ordination analysis showed that mud crabs adapt their diet according to environmental constraints. Furthermore, the results indicate that mud crabs showed opportunistic predation behavior as they were observed preying on other Portunidae species sharing the same trophic guild. Overall, these findings demonstrate the dietary plasticity and associated parasite infestation of an important crustacean predator, and provide evidence that environmental changes may affect incidences of the associated parasites as well as the specific predator-prey interactions indirectly through fluctuations in marine ecosystems.